Large-scale mass wasting in the western Indian Ocean constrains onset of East African rifting - Vittorio Maselli (Nature Portfolio, 2020)
The authors describe a huge submarine landslide deposit offshore Tanzania and highlight that large and potentially tsunamigenic landslide events are associated with plateau uplift and continental rifting in East Africa.